(untitled) (Eurasian Research Bulletin, 2026)
This article analyzes the priority areas of improving tax administration in the Republic of Uzbekistan, in particular, the issues of digitization of the tax system, implementation of international standards (OECD) and optimization of tax control. During the study, specific solutions were proposed to reduce the human factor in selecting candidates for tax audits, accelerate analytical processes using "Big Data" technologies, and expand the tax base in the field of e-commerce. It also covers mechanisms for reducing the administrative burden by introducing a tax monitoring system for large taxpayers and establishing cooperation with taxpayers based on mutual trust.